South African Anglican Military Chaplains and the First World War. Issue 2 (2nd April 2016) - Houston, Peter
Abstract: The role and value of Anglican chaplains in the military is a contested discourse. Anglican ministers have acted as chaplains to the military in South Africa since the earliest days of British colonialist expansion. At the outbreak of the First World War they joined ministers from a number of other denominations and saw action in the South West African and East African campaigns as well as in the trenches of Europe. Tensions arose around serving the aims of the military hierarchy while also challenging that same hierarchy at times. There was a major point of departure between Britain and South Africa on whether carrying arms was compatible with Holy Orders. This article seeks to bring to the fore many of these tensions, a subject that while given significant attention in Britain, is lagging behind in historical research in South Africa, where little has been published that focuses solely on South African Anglican military chaplains in the First World War.